Translation Errors of Noodles Product Cooking Instructions from Indonesian into English - Dwiyanto, Agus; Setianingrum, Diah Ayu (Universitas Islam Negeri Raden Intan Lampung, 2020)
This paper discussed the translation errors in various top brands of instant noodles in Indonesia, ranging from the products produced by the local industries to the one imported from overseas. In this research, the researchers used a descriptive qualitative research method. The sources of data mean for the objects of the research were ten cooking instructions or procedures of various brands of instant noodles in Indonesia, translated from Indonesian into English. The data were collected through documentation techniques. The types of data were words, phrases, and sentences. The data were classified and tabulated based on the error types, following the standard of ATA’s Framework for Standard Error Making Classification. The result of the analysis showed that there were 40 translation errors found in 10 of 23 error categories with Omission as the most frequent error produced. The three most prominent error categories found in the instant noodles’ cooking instructions are Omission, Mistranslation, Syntax, and Cohesion. Omission turns to be the highest category of translation errors, which appeared 13 times out of 40 errors or 32.5 % of errors found in the analysis, followed by Mistranslation with 15% and Syntax and Cohesion that shares the same percentage of findings by reaching 12.5%. The researchers also found out that out of 10 instant noodles brands, instant noodle brand D has the most translation errors with 9 error findings out of 40 errors in total, followed by brand J with 8 findings of errors.